Word‑level replacive tonal patterns in mande nominal constructions: On Christopher Green’s binary typology - Maria Konoshenko (Mandenkan, 2018)
The paper criticially discusses Green’s (this issue) binary typology of replacive tones in Western Mande nominal constructions. Green’s distinction between the two types of replacive tones in Western Mande is based on the existence of Word 2 to Word 2 tone spreading, which is attested in a subset of languages under the scope of Green’s paper. I suggest to shift the focus of Mande replacive tone typology from Word 2 to Word 2 tone spreading, as put forward by Green, to the properties of Word 2 tonal neutralization. The crucial evidence in favour of my approach comes from other Mande branches not discussed in Green’s paper. I argue that there are two types of Word 2 tonal neutralization in Mande. The first type covers phonological neutralization, whereby Word 2 gets a default (unmarked) tone and/or it may get its tone from Word 2 via spreading, this type is attested in Central Mande. The second type is morphological (morphosyntactic) neutralization whereby Word 2 is assigned a specific tone marker, typically low or extra‑low tone. This type of Word 2 neutralization is attested in Southern, Soso‑Southwestern Mande, Vai, and Soninke, although it is obscured by further surface W1 to W2 spreading in Soso‑Southwestern Mande and Vai.